Human language technology: challenges for computer science and linguistics 4th language and technology conference, LTC 2009, Poznan, Poland, November 6-8, 2009, revised selected papers - LTC 2009 (2009 Poznan, Poland); Vetulani, Zygmunt (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 4th Language and Technology Conference: Challenges for Computer Science and Linguistics, LTC 2009, held in Poznan, Poland, in November 2009. The 52 revised and in many cases substantially extended papers presented in this volume were carefully reviewed and selected from 103 submissions. The contributions are organized in topical sections on speech processing, computational morphology/lexicography, parsing, computational semantics, dialogue modeling and processing, digital language resources, WordNet, document processing, information processing, and machine translation.
Electronic reproduction.
Keywords: Computational linguistics -- Congresses; Semantic computing -- Congresses